Sustaining Employee Loyalty at PT Dua Kelinci in the Face of Economic Uncertainty: The Mediating Role of Job Satisfaction - Dian Ayu Maharani; Febrianur Ibnu Fitroh Sukono Putra (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2025)
An organization's inability to build employee loyalty amidst competitive business pressures can have a direct impact on productivity, operational efficiency, and the retention of key talent. This study aims to analyze the role of job satisfaction as a key mediator in increasing employee loyalty at PT. Dua Kelinci. This study used a quantitative approach with a survey method by distributing questionnaires to a total of 190 active employees of PT. Dua Kelinci. Data were analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The results showed that Motivation, job stress, and job satisfaction were proven to have a significant effect on employee loyalty, while the work environment, workload, and work rewards did not have a significant direct effect. However, the job satisfaction variable was able to significantly mediate the relationship between Motivation, job stress, work environment, and workload on employee loyalty, but did not significantly influence employee loyalty through job satisfaction. These findings confirm that job satisfaction is not only the result of good working conditions, but also a key factor in building and strengthening employee loyalty indirectly. Practically, this study provides an important contribution to companies in designing strategies to increase employee loyalty. Theoretically, this study enriches the literature on mediation mechanisms in employee behavior models, particularly in the context of the manufacturing industry.